Osseodensification: A New Era of Implant Osteotomy - Utkalika Das1, Gatha Mohanty2, Rinkee Mohanty3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Successful osseointegration is achieved by the primary and secondary stability of dental implants. Theprimary stability of any successful dental implant is dependent on the quality and quantity of bone. Besidesthe experience of the surgeon and bone-implant contact (BIC)at the time of implant placement is equallyimportant. Similarly the high insertion torque helps in obtaining primary stability. Several techniques havebeen introduced to enhance the bone quality and quantity in an attempt to achieve primary implant stability.One commonly used technique is under preparation of the osteotomy site by use of a drill that is one sizesmall than the implant diameter. However undersized osteotomy compromises the healing between the boneand implant and hampers secondary biological fixation. Osteotomes have also been used in an attempt toincrease the bone width buccolingually and improve the peri-implant site bone density. However studieshave reported that there was only an increase in bone density at the periapical area with no influence onthe lateral margins and primary stability of the implant. The associated trabecular fracture with osteotomebone condensation may further damage the osteocytes and cause extension microfracturesand delayedhealing. Finally,the success of implant therapy relies largely on the stability and mechanical durability ofthe prosthesis delivered to the patient. As such several modifications, reinforcements and techniques havebeen suggested over the years to optimize the same. The latest in line is the non-subtracting osteotomy byspecially designed Densah burs. This article aims to review the theory, advantages and disadvantages of thistechnique as compared to traditional osteotomy